Objective assessment of the speech quality broadcasted by local Digital Radio in selected locations in Wroclaw - Stefan Brachmański; Maurycy Kin; Natalia Rurzyńska (International Journal of Electronics and Telecommunications, 2024)
The development of digital radio, observed in recent years, and the advantages offered by this medium are resulting in the expansion of the audience. In order to ensure the proper quality of broadcasting, it is necessary to monitor this quality. The assessment based on listening tests is very expensive and organizationally inconvenient. The development of methods for objective evaluation of signals makes it possible to monitor the quality of transmitted content, without the need for troublesome procedures associated with subjective evaluation. The good correlation of subjective evaluation and objective measurements in the transmission of perceptually encoded signals, reported in the literature, may allow for random quality monitoring. The authors decided to test the feasibility of using two objective evaluation methods to assess the quality of the speech signal transmitted on digital radio by comparing the results obtained with the subjective evaluation. The paper presents the results of objective measurements of speech quality transmitted via Digital Audio Broadcasting+ in Wroclaw agglomeration. Measurements have been done in various city sites in order to determine the influence of the location on speech quality. The obtained results of the assessment performed by the use of two methods of testing: PESQ and POLQA, allowed to find a correlation between the objective and subjective results of quality evaluations. The method of objective testing may be used for monitoring the quality of signals in Digital Audio Broadcasting networks especially spoken broadcasts.